Factors that Impact Student Usage of the Learning Management System in Qatari Schools - Nasser, Ramzi; Cherif, Maha; Romanowski, Michael (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
In an attempt to enhance teacher and student performance in school, a learning management system (LMS) known as Knowledge-Net (K-Net) was introduced in Qatari independent schools. (All public schools in Qatar have transformed to independent schools; the independent schools model is similar to the charter school system in North America.) An LMS is a tool that organizes and regulates classroom administrative tasks, supports teachers and students in the teaching and learning process, and informs parents of their children’s progress and school activities. Despite the benefits of the LMS, research studies indicate that its use by students has been limited because of a number of manipulative and non-manipulative factors that can influence behavior. This study explores the factors that impact student use of the LMS K-Net in Qatari independent schools. Quantitative data were collected through a questionnaire that was administered to students in 37 schools. A total of 1,376 students responded to the questionnaire. Semi-structured interviews were used to collect qualitative data that helped to confirm the results of the quantitative data and to provide additional insight on students’ perspectives regarding the use of the LMS. The results point to a strong relation between ICT knowledge and LMS usage. They suggest that the more ICT knowledge students have, the less prone they are to using the LMS. Attitudinal barriers were not predictive of usage. Student usage was strongly correlated to teacher and parent usage. This study is informative in evaluating LMS usage in Qatari schools.